Optimal omegas – barriers and novel methods to narrow omega-3 gaps. A narrative review - Derbyshire, Emma J.; Birch, Catherine S.; Bonwick, Graham A.; English, Ashley; Metcalfe, Phil; Li, Weili (Frontiers in Nutrition, 2024)
Dietary intakes of omega-3 long chain polyunsaturated fatty acids (O3LC-PUFAs) such as eicosapentaenoic and docosahexaenoic acid are central to development and health across the life course. O3LC-PUFAs have been linked to neurological development, maternal and child health and the etiology of certain non-communicable diseases including age-related cognitive decline, cardiovascular disease, and diabetes. However, dietary inadequacies exist in the United Kingdom and on a wider global scale. One predominant dietary source of O3LC-PUFAs is fish and fish oils. However, growing concerns about overfishing, oceanic contaminants such as dioxins and microplastics and the trend towards plant-based diets appear to be acting as cumulative barriers to O3LC-PUFAs from these food sources. Microalgae are an alternative provider of O3LC-PUFA-rich oils. The delivery of these into food systems is gaining interest. The present narrative review aims to discuss the present barriers to obtaining suitable levels of O3LC-PUFAs for health and wellbeing. It then discusses potential ways forward focusing on innovative delivery methods to utilize O3LC-PUFA-rich oils including the use of fortification strategies, bioengineered plants, microencapsulation, and microalgae.